Specifically Increased Rate of Infections in Children Post Measles in a High Resource Setting - Bühl, Daniel; Staudacher, Olga; Santibanez, Sabine; Rossi, Rainer; Girschick, Hermann; Stephan, Volker; Schmidt, Beatrix; Hundsdoerfer, Patrick; von Moers, Arpad; Lange, Michael; Barker, Michael; Mall, Marcus A.; et al. (Frontiers in Pediatrics, 2022)
Objectives: Post-measles increased susceptibility to subsequent infections seems particularly relevant in low-resource settings. We tested the hypothesis that measles causes a specifically increased rate of infections in children, also in a high-resource setting. Methods: We conducted a retrospective cohort study on a large measles outbreak in Berlin, Germany. All children with measles who presented to hospitals in Berlin were included as cases, children with non-infectious and children with non-measles infectious diseases as controls. Repeat visits within 3 years after the outbreak were recorded. Results: We included 250 cases, 502 non-infectious, and 498 infectious disease controls. The relative risk for cases for the diagnosis of an infectious disease upon a repeat visit was 1.6 (95% CI 1.4 – 2.0, p < 0.001) vs. non-infectious and 1.3 (95% CI 1.1 – 1.6, p = 0.002) vs. infectious disease controls. 33 cases (27%), 35 non-infectious (12%) and 57 (18%) infectious disease controls presented more than three times due to an infectious disease (p = 0.01, and p = 0.02, respectively). This results in a relative risk of more than three repeat visits due to an infection for measles cases of 1.8 (95% CI 1.3 – 2.4, p = 0.01), and 1.4 (95% CI 1.0 – 1.9, p = 0.04), respectively. Conclusion: Our study demonstrates for the first time in a high-resource setting, that increased post-measles susceptibility to subsequent infections in children is measles-specific – even compared to controls with previous non-measles infections.